Face-on oriented hydrophobic conjugated polymers as dopant-free hole-transport materials for efficient and stable perovskite solar cells with a fill factor approaching 85%. Issue 7 (19th January 2022) - Liang, Lusheng; Shibayama, Naoyuki; Jiang, Haiying; Zhang, Zilong; Meng, Lingyi; Zhang, Lianjie; Wang, Can; Zhao, Nan; Yu, Yaming; Ito, Seigo; Wu, Jihuai; Chen, Junwu; et al.
Abstract : Siloxane-terminated polymers with low surface energy were studied as dopant-free HTMs in PSCs. The siloxane-terminated side-chains assisted the dissolution, tuning mobility, passivating perovskite defects and enhancing hydrophobicity of the polymer. Abstract : Developing high-performance dopant-free hole transport materials (DF-HTMs) is critical to realizing stable perovskite solar cells (PSCs). Herein, a class of siloxane-terminated polymers (PBZ-Si) with low surface energy were studied as DF-HTMs in PSCs. These polymers have good film-forming properties with unique face-on orientation and suitable valence bands. More importantly, the siloxane-terminated side-chains exhibited fantastic multifunctionality, providing the polymer with sufficient solubility, increased hole mobility, passivation capability, and hydrophobicity. Furthermore, for the first time, we observed directly the preferential face-on molecular orientation of polymeric HTMs on perovskite films by grazing incidence wide-angle X-ray scattering. Finally, planar n–i–p PSCs employing PBZ-3Si with complete siloxane-terminated side chains as the DF-HTM displayed a high efficiency of 20.18%, with an unprecedented fill factor up to 85%, a record fill factor value in all n–i–p PSCs with dopant-free HTMs. Moreover, the device with PBZ-3Si showed excellent thermal and moisture stability. The devices without encapsulation retained 76% of the initial efficiency after 333 h under 85 °C and 70 ± 10% relative humidity conditions. This work proves that siloxane-terminated side-chains are essential for the rational design of polymeric DF-HTMs toward efficient and stable PSCs.